Reconstructing the genetic history of Italians: new insights from a male (Y-chromosome) perspective*. (2nd January 2018) - Grugni, Viola; Raveane, Alessandro; Mattioli, Francesca; Battaglia, Vincenza; Sala, Cinzia; Toniolo, Daniela; Ferretti, Luca; Gardella, Rita; Achilli, Alessandro; Olivieri, Anna; Torroni, Antonio; Passarino, Giuseppe; et al.
Abstract: Background: Due to its central and strategic position in Europe and in the Mediterranean Basin, the Italian Peninsula played a pivotal role in the first peopling of the European continent and has been a crossroad of peoples and cultures since then. Aim: This study aims to gain more information on the genetic structure of modern Italian populations and to shed light on the migration/expansion events that led to their formation. Subjects and methods: High resolution Y-chromosome variation analysis in 817 unrelated males from 10 informative areas of Italy was performed. Haplogroup frequencies and microsatellite haplotypes were used, together with available data from the literature, to evaluate Mediterranean and European inputs and date their arrivals. Results: Fifty-three distinct Y-chromosome lineages were identified. Their distribution is in general agreement with geography, southern populations being more differentiated than northern ones. Conclusions: A complex genetic structure reflecting the multifaceted peopling pattern of the Peninsula emerged: southern populations show high similarity with those from the Middle East and Southern Balkans, while those from Northern Italy are close to populations of North-Western Europe and the Northern Balkans. Interestingly, the population of Volterra, an ancient town of Etruscan origin in Tuscany, displays a unique Y-chromosomal genetic structure.